Ascending aorta thrombus: A diagnostic and treatment dilemma. (July 2014) - Soo, Alan; Marley, Dominic; McGrath-Soo, Lorraine; Herron, Brian; Parissis, Haralabos
Due to its position, a mass lesion in the ascending aorta poses a diagnostic and treatment dilemma. We describe the management of a symptomatic mass in the ascending aorta in a 35-year-old man who presented with a cerebrovascular accident.